Non-industrial poultry farming in Morocco: A survey study in the Rabat-Salé-Kénitra Region - Asmae CHAHBI; El Mestafa EL HADRAMI; Hamid EL AMRI; Saâdia NASSIK; Ahmed DOUAIK; Mohamed BOUKHARTA (Revue Marocaine des Sciences Agronomiques et Vétérinaires, 2019)
Traditional poultry farming is an important alternative for the increase in the animal protein contribution in the rural environment. Surveys were carried outin 98 poultry farms in four provinces of the Rabat-Salé-Kénitra region to characterize the traditional poultry farming in this region. These surveys focused on the characteristics of the farms (socio-economic status of the farmer, the farming method, and the composition of the poultry, the avian species, the infrastructure, the business, the feed, the diseases, the mortality rate and the treatments used).The analysis of the collected data showed that women are primarily responsible for poultry farming (80%); 94.9% of the surveyed breeders have no technical training in poultry farming; the experience in the surveyed farms varies between 10 and 50 years (p <0.0001); high numbers of poultry are included in the majority (49%) between 20 and 100 individuals; poultry feed in the study areas was based primarily on natural resources (28%), followed by bran (23%) and wheat (22%); the most common diseases in the “Beldi chicken” are coccidiosis (22%) and avian influenza (21%), followed by E. coli (16%) and smallpox (11%). The majority of breeders practice traditional treatments (63%), whereas only 37% of breeders used veterinary treatments (p <0.001). Thus, poor production performance is recorded in these farms: a median mortality rate of 10% is related to the characteristics of the farms and farmers (Technical training, level of hygiene practiced in farms, etc.). Diseases, lack of supervision and financial means are the main constraints of the sector.